A mirror for magistrates and the politics of the English Reformation - Lucas, Scott (Massachusetts studies in early modern culture, 2009)
A memorial of suche princes: creation and contexts -- The consolation of tragedy: "Edmund Duke of Somerset," "Humfrey Duke of Gloucester," and the fall of the "Good Duke" of Somerset -- "Syr Thomas of Wudstocke" and the "unfortunate" death of Edward Seymour, Duke of Somerset -- A memorial of suche Princes and the loss of Imperial England -- Royal power and the abuse of the law in A memorial of suche Princes -- The seconde parte of the Mirrour for magistrates and the future of political literature in Elizabeth's reign -- Conclusion: The Mirror and its legacy -- Appendix: The growth and development of William Baldwin's A mirror for magistrates